A Brief history of the formative years of the Recreation Discipline at the University of Wisconsin - La Crosse, 1944-1968 - Krumenauer, Kay (My University, 1986)
This study traced significant events which occurred within the recreation discipline at the University of Wisconsin - La Crosse from its inception in 1944 through 1967. Significant events included: state recreation leaders requesting that La Crosse establish a recreation leadership training program to help meet the growing recreational needsof society after World War II; formulation and approval of the first recreation curriculum, a double major in physical education and community recreation; hiring new staff; student activities including establishment of the Recreation Majors Club in 1960; developing and refining new recreation courses and curriculum into a non-teaching major in 1962; the establishment of the Department of Recreation and Parks in 1967; and the development of two major areas of concentration in Recreation and Park Administration and Recreation Program Leadership.
Keywords: University of Wisconsin--La Crosse. Recreation and Parks Management Dept. -- History; Recreation leadership -- Study and teaching (Higher) -- Wisconsin -- La Crosse